2021
DOI: 10.1111/apha.13661
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis‐induced activation of distal nephron principal cells triggers Gdf15 secretion and adaptive proliferation of intercalated cells

Abstract: AimType A intercalated cells of the renal collecting duct participate in the maintenance of the acid/base balance through their capacity to adapt proton secretion to homeostatic requirements. We previously showed that increased proton secretion stems in part from the enlargement of the population of proton secreting cells in the outer medullary collecting duct through division of fully differentiated cells, and that this response is triggered by growth/differentiation factor 15. This study aimed at deciphering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 75 publications
1
37
0
Order By: Relevance
“…Principal cells secrete GDF15 in response to acidosis which then stimulates type A intercalated cell proliferation. GPR4 is not required for acidosis-induced GDF15 secretion but for its action on type A intercalated cells [12]. Whether the link between GPR4 and GDF15 extends beyond the kidney remains to be addressed.…”
Section: Gpr4 and Ogr1 And Renal Functionmentioning
confidence: 99%
“…Principal cells secrete GDF15 in response to acidosis which then stimulates type A intercalated cell proliferation. GPR4 is not required for acidosis-induced GDF15 secretion but for its action on type A intercalated cells [12]. Whether the link between GPR4 and GDF15 extends beyond the kidney remains to be addressed.…”
Section: Gpr4 and Ogr1 And Renal Functionmentioning
confidence: 99%
“…For example, TASK2 knockout mice display a phenotype similar to human proximal renal tubular acidosis [ 126 ], and OGR1 knockout mice display poor coordination between urinary acidification and calcium excretion [ 58 ]. GPR4 deficiency in mice fully blunts acid-dependent proliferation of type A intercalated cells and induction of transporters involved in acid–base balance in these cells [ 27 ]. These animals also show lower excretion of titratable acids and lower ammonium excretion in response to acid load [ 117 , 118 ].…”
Section: Additional Mechanismsmentioning
confidence: 99%
“…These animals also show lower excretion of titratable acids and lower ammonium excretion in response to acid load [ 117 , 118 ]. However, this might be indirectly caused by the respiratory acidosis of central origin observed in these animals [ 27 , 66 ]. The role of pH sensing is also extended to kidney injury conditions, as seen in the inhibition of ASIC1a with psalmotoxin 1 (PcTx1) in mice, which attenuated injury caused by renal ischemia reperfusion [ 109 ].…”
Section: Additional Mechanismsmentioning
confidence: 99%
“…The classical receptor for GDF15 is GFRAL that mediates most of its central nervous effect and metabolic effects (for review, see (26)). However, this receptor is not present in the kidney (25) but we have recently identified that ErbB2 receptor, another receptor of GDF15 was present in the kidney (25). In Figure 4B, we measured ErbB2 expression in whole kidney and isolated segments of the distal nephron from the connecting tubules (CNT) to the cortical (CCD) and medullary collecting duct (OMCD).…”
Section: Gdf15 Participates In the Renal Adaptation To K + -Restricti...mentioning
confidence: 99%
“…Here, we cannot definitively conclude for the involvement of GDF15 in one mechanism or another, but we believe that the apparition of doublets of ICA and their reduction in its absence rather plead for a role in the proliferation of ICA. The absence of GDF15 impedes the increase of ICA number in response to K + restriction, by a mechanism that, as in acidosis (25), involves ErbB2 receptor. In most of the peripheral tissues such as kidneys, the GDF15 receptor GFRAL is absent (42), indicating that the peripheral action of this factor must be transduced by another receptor.…”
Section: Gdf15 Regulates Renal Ion Excretionmentioning
confidence: 99%